FC 102PD INDUCED ARTERIOLAR AND PERITONEAL PATHOMECHANISMS ARE PARTIALLY REVERSED AFTER KIDNEY TRANSPLANTATION. (29th May 2021) - Zhang, Conghui; Bartosova, Maria; Schaefer, Betti; Herzog, Rebecca; Cerkauskiene, Rimante; Vondrak, Karel; Oh, Jun; Klaus, Günter; Zaloszyc, Ariane; Ariceta Iraola, Maria Gema; Ranchin, Bruno; Bayazit, Aysun Karabay; et al.
Abstract: Background and Aims: Due to the unphysiological composition of PD fluids, chronic peritoneal dialysis (PD) induces progressive peritoneal fibrosis, hypervascularization, and vasculopathy. The evolution of the PD membrane and vasculopathy following kidney transplantation (KTx) is largely unknown. Method: Arteriolar and peritoneal tissues were obtained from 107 children with chronic kidney disease (CKD5), 72 children on PD (treated with neutral pH PD fluids, with low glucose degradation product content, GDP) and 21 children, who underwent KTx 4-5 weeks after a median 21 months of PD. Specimen underwent standardized digital quantitative histomorphometry. Molecular mechanisms were studied in omental arterioles microdissected from surrounding fat by multi-omics followed by Gene Set Enrichment Analysis (GSEA); key findings were validated in parietal tissues of independent, matched cohorts by quantitative immunohistochemistry (n=15/group). Results: Arteriolar transcriptome and proteome GSEA revealed suppression of leucocyte migration and T-cell activation / secretory pathways regulation, of sprouting angiogenesis biological processes and of epithelial proliferation and cell cycle after KTx as compared to PD. Lipid / fatty acid metabolism, autophagy and ATP synthesis pathways were activated. Transcriptome analysis including KTx, PD and CKD5 specifically attributed regulation of arteriolar lipid and fatty acid metabolism to transplantation and comprised 140 transcripts; their regulation was confirmed on the proteome level. Hub gene fatty acid synthase was identified by protein interaction analysis (string-db.org). 15 arteriolar genes activated by PD were inactivated after KTx and included glucose metabolisms and cytoskeleton related transcripts. 24 transcripts and 10 corresponding proteins induced by PD were still active after KTx and associated with biological processes related to TGF-ß signaling, fibrosis and mineral absorption. In line with arteriolar multi-omics findings, peritoneal hypervascularization induced by chronic PD was reversed after Tx to CKD5 level. CD45 positive tissue infiltrating leucocytes count was reduced by 40% and was independently associated with microvessel density in multivariable analysis including PD vintage, daily GDP exposure and recent KTx. Peritoneal lymphatic vessel density, submesothelial thickness, activated fibroblast, fibrin deposit, macrophage and EMT cell counts remained unchanged after KTx compared to PD. Arteriolar lumen to vessel ratios (a marker of vasculopathy) were similar in both groups. Vessel-homeostasis-related proteins in independent, matched cohorts demonstrated increased caspase-3 abundance in peritoneal arterioles after KTx. Arteriolar VEGF-A, thrombospondin, angiopoietin1/2, and hypoxia-inducible factor-1 (HIF-1a) were unchanged, while submesothelial HIF-1a and angiopoietin1/2 were decreased after Tx, favoring vessel maturation. The abundance of the key driver of fibrosis, TGF-ß-effector pSMAD2/3, was unchanged in the peritoneum and arterioles after Tx. Conclusion: Our multi-omics analyses of fat covered omental arterioles, not directly exposed to PD fluids, demonstrate inhibition of PD induced immune response and angiogenesis pathways, of glucose metabolism and cytoskeleton regulation to levels similar as seen in children with CKD5. Arteriolar lipid and fatty acid metabolism is selectively altered after KTx. Reversal of low GDP PD induced hypervascularization and inflammation of the parietal peritoneum after KTx, mirror molecular changes in omental arterioles, while profibrotic activity persists after KTx in omental arterioles and in the parietal peritoneum.